KOMPETENSI GURU DAN MOTIVASI MENGAJAR GURU BERPENGARUH TERHADAP EFEKTIVITAS PEMBELAJARAN DI SMK NEGERI 3 KOTA SERANG - Dewi Surani; Mifthahudin Mifthahudin (Tarbawi, 2018)
This research to find out the influence of teacher competence and motivation in teaching towards the effectiveness of learning at SMK Negeri 3 Serang City. This research used quantitative approach with survey method with 53 teachers as samples. The samples were taken by a saturated sampling technique in which the total population was sampled. Data analysis techniques use classical assumption test, multiple linear regression and coefficient of determination analysis. The results showed that: (1) Teachers professional competence influence the effectiveness of learning with the determination coefficient 0.189 or 18.9%. (2) Teaching motivation influence the effectiveness of learning with the determination coefficient 0.388 or 38.8%. and (3)Teachers profesional competence and Teaching motivation influence simultaneously toward the effectiveness of learning with the value of coefficient determination 455 or 45.50%. Keywords. Teacher competence, teacher teaching motivation, effectiveness of learning